Prevalence of Peri-Implantitis Among the Patients Visiting REU Clinics - Basaad, Sulaiman; Alghunaim, Meshal; Alshehri, Talal; Alamode, Mohammed; Aljaser, Abdulah; Tayeb, Hussam; Alhussain, Badr; Ansari, Shahzeb H. (International Journal of Health Sciences, 2023)
Purpose: Periimplantitis is among the most common problems that can contribute to implant failure. Implant failure is linked to unattached, mobile oral mucosa, whereas the palatal masticatory mucosa is much more resistant to infection. The study aimed to determine the prevalence of peri-implantitis among the patients visiting REU clinics and compare the prevalence on the basis of gender, age, periodontal health and habits (smoking). Methodology: This is a retrospective study done using the patients' files. Convenient sampling will be done and 284 patients' files were selected from Implantology department. Bone loss of 4mm or more is mild, 6mm or more is moderate and 8mm or more is severe. Results: 45% of the 284 patients examined had peri-implantitis, with prevalence increasing significantly with age. Regarding the severity, 66.4% had mild, 25.8% had moderate and 7.8% had severe type of peri-implantitis. The prevalence of peri-implantitis is very high among the patients' received implants in REU. Incidence of peri-implantitis increases significantly with the old age. Unique Contribution to Theory, Policy and Practice: This study reveals a high peri-implantitis prevalence (45%) in REU clinics, with a significant association to age but not smoking or gender. It highlights the need for improved prevention, management, and further investigation into underlying factors and risk associations.